Risk factors for post-operative complications after sentinel lymph node biopsy for cutaneous melanoma: Results from a large cohort study. Issue 12 (December 2019) - Lindqvist, E.K.; Laine, E.; Kamali, A.; Sars, C.; Gillgren, P.; Schultz, I.
Summary: Background: A sentinel lymph node (SLN) biopsy is a common surgical procedure for cutaneous melanoma. Our aim was to evaluate risk factors for early post-operative complications after SLN biopsy and to examine the impact of complications on health care resource utilisation. Methods: We performed a retrospective cohort study including all adult patients who underwent a SLN biopsy for cutaneous melanoma in the Stockholm region from 2006 to 2014. Data of patient and tumour characteristics were collected from medical records, as well as information on complications and outpatient visits within 30 days from surgery. Risk factors were evaluated through logistic regression. Results: Out of 886 patients who underwent SLN biopsy during the study period, 109 (12.3%) had one or several post-operative complications. The most common complication was a wound infection (7.7%), followed by seroma (6.4%). The risk of a post-operative complication was increased in patients with diabetes (odds ratio (OR) = 10.0, 95% confidence interval (CI) 4.0–24.6), who had inguinal location of SLN (OR = 2.7, 95% CI 1.7–4.3), who were male (OR = 1.9, 95% CI 1.2–2.9) and who had ulceration of the primary tumour (OR = 1.6, 95% CI 1.0–2.6). Individuals with post-operative complications had more visits to the outpatient clinic ( p < 0.05). Conclusion: Complications after SLN biopsy affect 12.3% of patients. Our results suggest that patients with diabetes, who had inguinal SLN biopsy and who were male have increased risk, and this might warrant more intense post-operative surveillance.